2016
DOI: 10.1097/cji.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

An Association Between Glatiramer Acetate and Malignant Melanoma

Abstract: A 43-year-old female receiving immunomodulatory therapy with glatiramer acetate (copaxone, GA) for relapsing, remitting multiple sclerosis was diagnosed with stage IIIB melanoma that recurred <7 months after resection and lymphadenectomy. In preparation for systemic therapy the patient discontinued GA, and shortly thereafter experienced spontaneous and complete clinical and radiographic resolution of her disease. The development and subsequent regression of melanoma in this patient may be due to the use and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Other studies have not found a significant association between GA and breast cancer (16,39). Several skin cancers have been reported in patients on GA, including one case study of primary cutaneous anaplastic large-cell lymphoma and one case study of melanoma (44,45).…”
Section: Glatiramer Acetate (Copaxone)mentioning
confidence: 96%
“…Other studies have not found a significant association between GA and breast cancer (16,39). Several skin cancers have been reported in patients on GA, including one case study of primary cutaneous anaplastic large-cell lymphoma and one case study of melanoma (44,45).…”
Section: Glatiramer Acetate (Copaxone)mentioning
confidence: 96%
“…Glatiramer acetate was introduced in the mid-1990s, mainly for the recurrent-remissive form of MS. Its administration is not related to the incidence of cancers, but it has been attributed to a slight increase in the number of breast cancers 6 . One article reported a 43-year-old woman who presented with stage IIIb melanoma, with spontaneous remission at the time of treatment discontinuation, in whom glatiramer acetate was associated with skin cancer 42 . Teriflunomide, the oral therapy for MS, has been associa ted with lymphoma, and it may be possible to correlate with breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there has been an increase in incidence of malignancy seen in MS patients treated on with immunomodulant therapies that need further investigation 9 - 12 , 19 - 22 , 30 - 34 (refer Table 2 ). Given that MS patients can be exposed to many medications over the course of the disease with different mechanisms of action, these can eventually alter the immune system, which indirectly increases their cancer potential.…”
Section: Discussionmentioning
confidence: 99%